Public Administration Ethics in the Administration of Governance in Indonesia - Yofitri Heny Wahyuli (Universitas Sebelas Maret, 2021)
Ethics is an important element determining the successful implementation of organizational activities and public administration actors. The importance to implement public administration ethics in the Indonesia government bureaucracy was based on ethical problems occurring, such as corruption, collusion and nepotism. This research used qualitative method, in which primary data was obtained from observations, and secondary data from media and literature study. From the research conducted, it can be seen that few government officials in Indonesia are less accountable for performing their duties, authorities and responsibilities and as a result the public bureaucracy in the reform era was much highlighted by the public and got criticism. To solve this problem, besides enforcing the laws, the government also must cultivate and implement the public administration ethics to their bureaucratic apparatus.